Exploration of Core Symptoms for the Diagnosis of Alcohol Dependence in the ICD‐10. (26th September 2016) - Yoshimura, Atsushi; Komoto, Yasunobu; Higuchi, Susumu
Abstract : Background: The classification of alcohol use disorder has changed over the past century. Now, the conceptualization of alcohol dependence is still controversial. Accumulating evidence has shown the reliability and validity for the diagnosis of alcohol dependence in the ICD‐10 and DSM‐IV. However, the meaning and association of the respective diagnostic items, which are descriptive of representative symptoms, have hardly been examined. The core symptom of substance use disorder has been debated in various situations, but has never been elucidated logically. Methods: We consecutively registered 192 patients with alcohol‐related problems who visited our hospital for the first time during a certain period. The relations and principal components among the checked items of the ICD‐10 diagnostic criteria were examined statistically. Results: Three diagnostic items in the ICD‐10 were strongly correlated with each other and were thought to form the core symptoms of alcohol dependence: "strong desire, " "difficulties in controlling, " and "neglect of pleasures." One major physical phenomenon, "withdrawal, " seemed to complement the core symptoms in the diagnosis of alcohol dependence. Another physical phenomenon, "tolerance, " was demonstrated to be a relatively independent item. The principal component analysis also demonstrated that the diagnostic item "difficulties in controlling" had the maximum component loading value, followed by 2 items, "neglect of pleasures" and "strong desire." Conclusions: The core symptomatic elements in the diagnosis of alcohol dependence were statistically suggested in this study. Knowledge of the relations and components among the diagnostic items of alcohol dependence might also be applicable to other forms of substance use dependence and behavioral addiction. Abstract : Correlation diagram showing diagnostic criteria items of alcohol dependence in the ICD‐10, which were observed among patients with alcohol‐related problems at the time of first visit to the hospital. Three diagnostic items in the ICD‐10 were strongly correlated with each other and were considered to form the core symptoms for the diagnosis of alcohol dependence: "strong desire, " "difficulties in controlling, " and "neglect of pleasures."